PENEGAKAN HUKUM YANG BERORIENTASI PADA KEBERLANJUTAN SUMBER DAYA IKAN - Rochmani, Rochmani (Jurnal Media Hukum, 2014)
AreaÂ  ofÂ  IndonesiaÂ  consists ofÂ  80% water, whichÂ  containsÂ  abundanceÂ  ofÂ  potentialÂ  fishÂ  resources,Â  ThoseÂ  fish resourcesÂ  shouldÂ  beÂ  utilizedÂ  forÂ  as muchÂ  asÂ  prosperityÂ  and welfareÂ  forÂ  Indonesian.Â  InÂ  fact,Â  fishÂ  resourceshavenât enhanced theÂ  livingÂ  standard, whichÂ  isÂ  sustainable and equitable.Â  Issues on fisheries come up such as exaggerationÂ  ofÂ  fishing,Â  theftÂ  fish,Â  illegalÂ  fishingÂ  activitiesÂ  andÂ  theÂ  useÂ  ofÂ  fishÂ  resourcesÂ  thatÂ  exceedingÂ  thegeneration of fishÂ  itself. ThatÂ  circumstance willÂ  cause harmÂ  forÂ  the state,Â  the fishermen, as well as peopleÂ  in general.Â  TheÂ  useÂ  ofÂ  toolsÂ  thatÂ  harmÂ  theÂ  nature willÂ  causeÂ  theÂ  decreaseÂ  ofÂ  fishÂ  resourcesÂ  andÂ  threatÂ  thesustainabilityÂ  ofÂ  fishÂ  resources.Â  TheÂ  aimÂ  ofÂ  writingÂ  thisÂ  articleÂ  isÂ  toÂ  analyzeÂ  lawÂ  enforcementÂ  relatedÂ  toÂ  the sustainability of fishÂ  resources and the sustainability ofÂ  fishÂ  resources, viewed fromÂ  the perspective ofÂ  justice.As the result ofÂ  the study,Â  law enforcement to protect theÂ  fish resources generally has not given attentionÂ  to theÂ  sustainability ofÂ  fishÂ  resources,Â  thereforeÂ  fishermenÂ  stillÂ  useÂ  unfriendlyÂ  toolsÂ  toÂ  catchÂ  theÂ  fishes.Â  ThoseunfriendlyÂ  tools willÂ  causeÂ  theÂ  occurrenceÂ  ofÂ  over-fishingÂ  and willÂ  impactÂ  toÂ  theÂ  environmentalÂ  damages. ThoseÂ  kinds ofÂ  things will destructÂ  theÂ  fishes,Â  thereforeÂ  theÂ  quantityÂ  ofÂ  fish willÂ  have deteriorated and evencouldÂ  beÂ  extinct.Â  ThoseÂ  environmentalÂ  damages wouldÂ  sufferÂ  theÂ  present generationÂ  as wellÂ  asÂ  theÂ  next generationÂ  sinceÂ  theyÂ  couldnâtÂ  consumeÂ  fish whichÂ  isÂ  veryÂ  essentialÂ  forÂ  theÂ  growthÂ  ofÂ  the human bodyÂ  anderadicateÂ  the job for the people as the fishermen. The present generation will be sinful if the next generation will getÂ  theÂ  impact of whatÂ  the present generation done.Â  In orderÂ  toÂ  reduce more over-fishing activities and theÂ  distrustÂ  ofÂ  theÂ  fish habitatÂ  itÂ  needsÂ  theÂ  lawÂ  enforcement, whichÂ  is orientedÂ  toÂ  theÂ  sustainability ofÂ  fish resources.Â  TheÂ  sustainabilityÂ  ofÂ  fisheryÂ  resourcesÂ  couldnât maintainÂ  itsÂ  existence,Â  thisÂ  couldÂ  beÂ  seenÂ  asÂ  the symbolÂ  ofÂ  environmentalÂ  damages.Â  InÂ  thisÂ  case,Â  theÂ  lawÂ  alsoÂ  needsÂ  to makeÂ  integrationÂ  ofÂ  fishÂ  resources sustainability to be processed so thatÂ  it willÂ  result outputÂ  law enforcement which is oriented toÂ  fish resourcessustainability.Â  AsÂ  aÂ  conclusion,Â  inÂ  lawÂ  enforcementÂ  orientedÂ  toÂ  fishÂ  resourcesÂ  sustainability,Â  itÂ  needsÂ  toÂ  be thought by the lawmaker to embed that the law should containÂ  idea or concept about justice,Â  legal certainty,the significance of fish resources and the implementation of the law itself. In the fish resources utilization and law enforcements, it needs to pay attention to the justice principle; intergenerational equity; intergenerational equity;Â  precautionary;Â  conservationÂ  ofÂ  biologicalÂ  diversity;Â  conservationÂ  ofÂ  biologicalÂ  diversity.